Comparison of fluidised bed and spouted bed for the combustion of rice husk - Looi, Yat Seong (2005)
The purpose of this study was to evaluate the characteristics and performance of fluidised and spouted bed for the combustion of rice husk. With the annual generation rate of rice husk of approximately 0.4 million metric tones in Malaysia, disposal of the husk was a problem. The calorific value of the husk and the amorphousity of the ash make combustion the better option due to the vast reduction in volume of rice husk and control in combustion temperature. Numerous combustion systems are currently available but fluidised and spouted beds have numerous advantages over the other systems. Hydrodynamic studies show that sand size range of 0.30 mm to 0.50 mm and 0.50 mm to 0.71 mm are suitable as the bed material for fluidised and spouted bed respectively. Combustion studies were conducted in a 90 mm OD combustor fitted with a 60Â° conical base using commercial sand grade 20/30 and 30/60. Autogenous combustion could be achieved at air factor 0.7 to 1.5 (static bed height = 0.5Dc) in a fluidised bed and at air factor 1.0 to 1.5 (static bed height = 1.5Dc) for a spouted bed fitted with a draft tube (SBDT). However, the study showed that combustion could not be achieved with the conventional spouted bed. Fluidising velocities of 4.5Umf to 6Umf and spouting velocities of 1.75Ums to 2.85Ums were optimised for autogenous combustion. Higher bed temperature was observed for fluidised bed combustion of rice husk. XRD analysis further showed that fluidised bed fly ash was amorphous. Performance evaluation revealed that fluidised bed was a better option than spouted bed. Autogenous combustion and amorphous ash could also be achieved when combustion was conducted in a large-scale fluidised bed (210 mm ID, static bed height = 0.5Dc, sand 30/60). This study demonstrated that fluidised bed was suited for the combustion of rice husk compared to the spouted bed.